97.3k views
0 votes
Solve for y in terms of x: 3y-2x=7 Show work!

User Lolly
by
4.4k points

2 Answers

3 votes

Answer:

y = ⅓(2x + 7)

Explanation:

3y - 2x = 7

3y = 2x + 7

y = ⅓(2x + 7)

User Sevi
by
4.7k points
3 votes

Answer:

y = (2/3)x + 7/3

Explanation:

First we want to isolate 3y on the left side. To accomplish this, add 2x to both sides. The result will be 3y = 2x + 7.

Next we divide all three terms by 3 to complete the isolation of y on the left side:

y = (2/3)x + 7/3

User Pfn
by
5.4k points